IDENTIFIKASI KESESUAIAN LOKASI TEMPAT PEMAKAMAN UMUM DI KECAMATAN SINGKAWANG BARAT - Ratna Juwita, Dewi; Wulandari, Agustiah; Zulkifli Mulky, Gusti; Sophia Lubis, Mira (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
The distribution of locations for public cemeteries in West Singkawang Sub-District largely ignores the location suitability provisions based on Government Regulation Number 9 of 1987. One of them is the Al-Firdaus Islamic TPU in Tengah Kelurahan because it is close to settlements. The purpose of this study was to identify the suitability of the location of the distribution of public cemeteries in West Singkawang District and provide recommendations for locations for the provision of new public cemeteries. This study used a quantitative approach with overlay and scoring analysis techniques. The results of this study were obtained from six public cemeteries, only one of which had a